Transoesophageal electrocardiography features in patients with atrioventricular nodal reentrant tachycardia - A. V. Tarasov; K. V. Davtyan; Yu. M. Pozdnyakov (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study diagnostic value of transoesophageal electrocardiography (TE ECG) in verifying double physiology of atrio-ventricular (AV) node in differential diagnostics of supraventricular tachycardias (SVT), as well as in assessment of diagnostic specifics among patients with paroxysmal AV nodal reentrant tachycardia (PAVNRT).Material and methods. To diagnose SVT, 391 TE ECG procedures were performed; in 234 patients, PAVNRT diagnosis was confirmed. The present study included 49 PAVNRT patients: 34 (69,4%) women and 15 (30,6%) men; mean age 52,6±24,6 years; mean arrhythmia duration 11,6±8,9 years. TE ECG was performed according to a standard protocol; afterwards, intracardiac (IC) ECG and radioablation (RA) were performed at a Cardiosurgery department. Finally, the protocols of TE and IC ECG were compared.Results. TE ECG demonstrated some specific features of AV node physiology and higher sensitivity and specificity in PAVNRT diagnostics. However, TE ECG was inadequately effective in verifying double physiology of AV node in PAVNRT patients with “inseparable” AV conduction curve or with wide QRS tachycardia. Moreover, TE ECG potential was limited in differential diagnostics between PAVNRT and orthodrome AV tachycardia with involvement of left posterior additional branch. To identify specific SVT types, AV conductivity character, atrial activation sequence, and VA conductivity time in tachyarrhythmia should be analysed. Since all these criteria have low specificity, they should be considered in combination only.Conclusion. IC ECG remains the “gold standard” in diagnosing electrophysiological mechanisms of paroxysmal tachycardias. However, TE ECG data ply an important role in PAVNRT diagnostics. Specificity of the latter method influences indications and contraindications for intervention, as well as affects RA complication prognosis.